Health development and health reform: Where to from here? - Briggs, DS (Journal of Public Health and Development, 2020)
Health Development has been a part of the health system lexicon for a considerable period and had currency particularly in the aid context to those countries attempting to improve the health status of their populations. The language had changed to ‘health reform’ in the first decade where in the period to 2010 the focus of government was often on constraining activity as a means of controlling costs with an emphasis on managing waiting lists and times, rather than developing the health outcomes of populations. The emphasis of health reform was on consolidation of organisations into larger and distant geographic concentrations. Reform has been less about the detailed design of specific interventions than about the management of institution building in a context of complexity and rapid change. Existing definitions minimises the role of the human capacity to cope autonomously with life’s ever changing physical, emotional, and social challenges and to function with fulfilment and a feeling of wellbeing with a chronic disease or disability. This movement in health development towards societal contexts is increased when we use the language of holistic care philosophy which acknowledges the close relationship between body, mind and soul (spirit) with a focus on individualism, emphasizing that every dimension of a human is distinctive and unique as well as being connected to each other. An institutional based contemporary health system should consider health development and health reform within a framework that encompasses a wider societal context that is based on trusting relationships within a wider community and organisational settings that place valuing health above healthcare and that have a wholistic, patient centred focus.